Effects of propofol versus isoflurane on liver function after open thoracotomy. (March 2015) - Dabir, Shideh; Mohammad-Taheri, Zohreh; Parsa, Tahereh; Abbasi-Nazari, Mohammad; Radpay, Badiozaman; Radmand, Golnar
Background: Anesthetic agents and type of surgery may contribute to postoperative hepatic injury. Inhalational anesthetics have been associated with hepatic dysfunction after surgery, however, propofol is expected to have a lower potential for postoperative liver injury. This prospective double-blind randomized clinical study was planned to determine whether postoperative liver function differs after anesthesia with isoflurane and total intravenous anesthesia with propofol in patients undergoing a posterolateral thoracotomy. Methods: Eighty-eight patients in American Society of Anesthesiologists physical status 1 or 2, aged 16–60 years, and scheduled for an elective posterolateral thoracotomy, were randomly assigned to an anesthetic protocol: propofol ( n = 44) or isoflurane ( n = 44). Induction of anesthesia was similar in both groups. Serum levels of aspartate aminotransferase, alanine aminotransferase, alkaline phosphatase, lactate dehydrogenase, total bilirubin, and γ-glutamyltransferase were measured before induction of anesthesia and on the first and third days after either propofol or isoflurane anesthesia. Results: Mild changes in postoperative serum levels of liver enzymes were significant within each group but the differences between groups were not significant. Conclusions: Propofol and isoflurane anesthesia have a comparable minor effect on liver function after an elective posterolateral thoracotomy.